The nematode Caenorhabditis elegans displays a chemotaxis behavior to tuberculosis-specific odorants. (August 2016) - Neto, Mário F.; Nguyen, Quan H.; Marsili, Joseph; McFall, Sally M.; Voisine, Cindy
Abstract: A simple, affordable diagnostic test for pulmonary tuberculosis (TB) is urgently needed to improve detection of active Mycobacterium tuberculosis. Recently, it has been suggested that animal behavior can be used as a biosensor to signal the presence of human disease. For example, the giant African pouched rats can detect tuberculosis by sniffing sputum specimens while trained honeybees respond to three of the volatile organic compounds (VOCs) detected in the breath of TB positive patients by proboscis extension. However, both rats and honeybees require animal housing facilities and professional trainers, which are outside the scope of most disease testing facilities. Here, we report that the innate olfactory behavioral response of the roundworm nematode Caenorhabditis elegans can be used to detect the TB-specific VOCs methyl p -anisate, methyl nicotinate, methyl phenylacetate and o -phenylanisole, in chemotaxis assays. Dauer larvae, a long-lived stress resistant alternative development state of C. elegans in which the animals can survive for extended periods of time in dry conditions with no food, were also demonstrated to detect the VOCs. We propose that exposing naive dauer larvae to TB-related VOCs and recording their response in this behavioral assay could lead to the development of a new method for TB diagnostics using breath as the sample type.